National identity and the integration of second-generation immigrants - Ole Monscheuer (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2020)
This paper studies the effect of immigrants' national identity on integration in an inter-generational context. Economic theory predicts that the origin country identity of immigrants affects their children's integration through its effects on social network choices and incentives to invest in country-specific human capital. Yet, it is difficult to identify these effects empirically due to potential endogeneity. The empirical analysis of this paper relies on a novel IV strategy inspired by the epidemiological approach, and exploits rich survey data from the U.S. Results show that children whose parents are strongly attached to their origin country have less contact to natives and develop a stronger origin country identity. Consistent with the theoretical argument, they speak English less frequently and more poorly, and perform worse in school compared to peers whose parents are less attached to their origin country. Additional results from the CPS suggest that there exist negative long-term effects on labor market outcomes.
Keywords: F22; J15; Z13; 330